От войны до войны: из цикла "Отблески Этерны". Кн. 2 / В. В. Камша - Камша Вера Викторовна (Эксмо, 2004)
Экземпляры: аб. (2021) / Инвентарный номер: 56524 / Цена: / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: К 18 / ББК: 84(2Рос=Рус)6